Assessment of Flood Risk Based on ISO Clustering and Maximum Likelihood Method --Taking Wuchuan City as an Example - LIU Yang; SONG Feiyan; LIN Kairong; LIN Bo (Renmin Zhujiang)
Under the background of global climate change, extreme weather,especially heavy rainfall and storm surge, is becoming an important influencingfactor of flood disaster in coastal areas, endangering the safety of localpeople's lives and property. Taking Wuchuan City as the researcharea, with towns and streets as units, this paper establishes the flood riskassessment model based on the assessment indexes from three aspects of factorrisk, vulnerability of hazard-bearing body, disaster prevention and mitigationability, conducts space overlay analysis through ArcGIS platform, divides theflood risk into micro, low, medium, high and extremely high with ISO clustering-maximum likelihood method, and classifies Wuchunan City into five risk areasaccording to the assessment results. The results indicate that: the flood disasterrisk in Wuchuan City is at the medium risk level as a whole, with a risk value of3.04, and higher in the mid-west region and lower in the southeast region for thespatial distribution. After comparison validation with the survey data of proneflood points in Wuchuan City, it is indicated that 91% of them are located in theextremely high-risk and high-risk areas, which shows that the assessment resultsare relatively accurate and can be great of reference for the prevention andcontrol of local flood disaster.